Risk‐Treatment Paradox in the Selection of Transradial Access for Percutaneous Coronary Intervention. Issue 3 (24th May 2013) - Wimmer, Neil J.; Resnic, Frederic S.; Mauri, Laura; Matheny, Michael E.; Piemonte, Thomas C.; Pomerantsev, Eugene; Ho, Kalon K. L.; Robbins, Susan L.; Waldman, Howard M.; Yeh, Robert W.
Abstract : Background: Access site complications contribute to morbidity and mortality during percutaneous coronary intervention (PCI). Transradial arterial access significantly lowers the risk of access site complications compared to transfemoral arteriotomy. We sought to develop a prediction model for access site complications in patients undergoing PCI with femoral arteriotomy, and assess whether transradial access was selectively used in patients at high risk for complications. Methods and Results: We analyzed 17 509 patients who underwent PCI without circulatory support from 2008 to 2011 at 5 institutions. Transradial arterial access was used in 17.8% of patients. In those who underwent transfemoral access, 177 (1.2%) patients had access site complications. Using preprocedural clinical and demographic data, a prediction model for femoral arteriotomy complications was generated. The variables retained in the model included: elevated age ( P <0.001), female gender ( P <0.001), elevated troponin ( P <0.001), decreased renal function or dialysis ( P =0.002), emergent PCI ( P =0.01), prior PCI ( P =0.005), diabetes ( P =0.008), and peripheral artery disease ( P =0.003). The model showed moderate discrimination (optimism‐adjusted c‐statistic=0.72) and was internally validated via bootstrap resampling. Patients with higher predicted risk of complications via transfemoral access were less likely to receive transradial access ( P <0.001). Similar results were seen in patients presenting with and without ST‐segment myocardial infarction and when adjusting for individual physician operator. Conclusions: We generated and validated a model for transfemoral access site complications during PCI. Paradoxically, patients most likely to develop access site complications from transfemoral access, and therefore benefit from transradial access, were the least likely to receive transradial access.